Personal qualities of social work specialists with different aspirations for career growth - Dvoretskaya, Viktoria A. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
Social work is a complex process that requires deep knowledge in the field of management theory, economics, psychology, sociology, pedagogy, medicine, law, etc. The effectiveness of social work depends not only on the level of training and experience of a social work specialist, but also on characteristics of his personality. The main requirements to the socio-personal and professional portrait of a social workers in modern society are considered. The criteria of professional suitability of social work specialists are determined, which can be useful for analysing the formation of the professional competence of a future social workers. The research of some personal qualities of social work specialists has been carried out. It was found that the majority of respondents strive for career growth (they plan to become social work methodologists or heads of one of organisations providing social services) and consider it is necessary to constantly improve in professional activity, regardless of whether there is a prospect of career growth.
Keywords: social work specialist; personal qualities; career growth; social sphere; professional suitability